2001
DOI: 10.2337/diacare.24.11.1957
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sibutramine in Obese Female Subjects With Type 2 Diabetes and Poor Blood Glucose Control

Abstract: OBJECTIVE -In this study, we evaluated the efficacy of sibutramine in combination with hypoglycemic drugs in obese type 2 diabetic women whose glucose levels were poorly regulated.RESEARCH DESIGN AND METHODS -Female patients with type 2 diabetes, poorly controlled glucose levels, and HbA 1c Ͼ8% were randomly assigned to one of two groups. In addition to their prescribed hypoglycemic agents (maximum doses of sulfonylureas and metformin), one group (n ϭ 30) received a placebo twice daily for 6 months and the oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(54 citation statements)
references
References 21 publications
2
51
0
1
Order By: Relevance
“…Modest weight loss leads to improvements in LDL-C, blood pressure, insulin resistance and left-ventricular mass. [201][202][203][204][205][206] (1++)…”
Section: Benefits Of Weight Loss Interventionmentioning
confidence: 99%
“…Modest weight loss leads to improvements in LDL-C, blood pressure, insulin resistance and left-ventricular mass. [201][202][203][204][205][206] (1++)…”
Section: Benefits Of Weight Loss Interventionmentioning
confidence: 99%
“…At least four short-term trials have evaluated the effect of sibutramine alone in obese people with type 2 diabetes (10,20 -22). All four trials found sibutramine produced greater weight loss than placebo; however, in only one trial was there a significant improvement in HbA 1c (21).…”
Section: Adverse Effectsmentioning
confidence: 99%
“…17 Sibutramine, a norepinephrine and serotonin reuptake inhibitor enhances satiety 18,19 and results in sustained weight loss in obese patients. [20][21][22][23][24][25][26][27] The aim of this randomised 12-month trial was to examine the effects of sibutramine 15 mg vs placebo on HRQL among obese patients with type II diabetes treated with hypocaloric diet for 12 months.…”
Section: Introductionmentioning
confidence: 99%